2019
DOI: 10.2147/opth.s184024
|View full text |Cite
|
Sign up to set email alerts
|

<p>Architecture evaluation of the main clear corneal incisions in femtosecond laser-assisted cataract surgery by optical coherence tomography imaging</p>

Abstract: Purpose To assess the stability and reliability of femtosecond laser-assisted cataract surgery (FLACS) incisions design and dimensions using anterior segment optical coherence tomography (AS-OCT) imaging. Setting Renato Ambrósio Ophthalmologic Study Center from Hospital Oftalmológico de Brasília, Brasília, Brazil. Design Prospective nonrandomized controlled case series. Methods Eyes undergoing FLACS with triplanar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…22 Triplanar incisions are more accurate and effective when using the femtosecond laser, achieving good wound coaptation without the need for additional hydration. 8,23 Single-plane incisions are easier to make; however, their tightness can be compromised in wide and shorter incisions. Arched single-plane incisions in which the length of the arcuate incision is longer than its incision chord appear to be safer in terms of wound tightness and the sliding of one lip over another.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Triplanar incisions are more accurate and effective when using the femtosecond laser, achieving good wound coaptation without the need for additional hydration. 8,23 Single-plane incisions are easier to make; however, their tightness can be compromised in wide and shorter incisions. Arched single-plane incisions in which the length of the arcuate incision is longer than its incision chord appear to be safer in terms of wound tightness and the sliding of one lip over another.…”
Section: Discussionmentioning
confidence: 99%
“…12 The total sealing surface damage of the incision and local DMD tend to appear spontaneously during the first few weeks after surgery, disappearing several months later. 8,12 Nevertheless, it seems that endothelial misalignment persists and increases in the late postoperative period. 12 Although there appears to be a consensus in the literature on the changes that occur in the architecture of main cataract surgery incisions, to the best of our knowledge, no studies have been published on the changes produced by astigmatic incisions without manipulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported a range of incidences for patients who had defective incisions. This might be due to the discrepancies in surgical techniques, including femtosecond laser-created CCI (Alio et al 2013;Grewal & Basti 2014;Chaves et al 2019), incision width (Li et al 2011;Li et al 2018), stromal hydration (Fukuda et al 2011;Bang et al 2015), postoperative drug usage (Choi et al 2016) and measuring principles. The frequency of the DMD and wound misalignment at 1 month was similar to previous studies (Wang et al 2012;Li et al 2018;Rodrigues et al 2019).…”
Section: Features Analysismentioning
confidence: 99%